2013
DOI: 10.3945/jn.112.168906
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet Supplementation with Methyl Donors and Increased Parity Affect the Incidence of Craniofacial Defects in the Offspring of Twisted gastrulation Mutant Mice

Abstract: Diets rich in methyl-donating compounds, including folate, can provide protection against neural tube defects, but their role in preventing craniofacial defects is less clear. Mice deficient in Twisted gastrulation (TWSG1), an extracellular modulator of bone morphogenetic protein signaling, manifest both midline facial defects and jaw defects, allowing study of the effects of methyl donors on various craniofacial defects in an experimentally tractable animal model. The goal of this study was to examine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…A recent study (Lubecka-Pietruszewska et al, 2013) showed that folic acid lead to down regulation of PTEN and APC which may be linked to the increased DNA methylation detected within their promoter regions. It may be explained by that folic acid as a methyl donor can directly increase the methylation (Billington et al, 2013). Another study has found that there was no significant change in the SERPINB5 expression when 50 mM of genistein was given to treat LNCap prostate cancer cell line (Merchant et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Lubecka-Pietruszewska et al, 2013) showed that folic acid lead to down regulation of PTEN and APC which may be linked to the increased DNA methylation detected within their promoter regions. It may be explained by that folic acid as a methyl donor can directly increase the methylation (Billington et al, 2013). Another study has found that there was no significant change in the SERPINB5 expression when 50 mM of genistein was given to treat LNCap prostate cancer cell line (Merchant et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several methyl donor diets were tested for their ability to rescue craniofacial defects in twisted gastrulation mutants [Billington et al, 2013]: these mutants have jaw defects (micrognathia and agnathia) with or without midline defects characteristic of holoprosence-phaly. The defects occur with incomplete penetrance (40% rate for all defects combined) on the C57BL/6 back-ground when dams are fed a control diet.…”
Section: Mechanisms and Mouse Models: Nutrient Modulation Of Neural Tmentioning
confidence: 99%
“…Since neural crest cells are the source of cranial mesenchyme, protective effect of diet on branchial arch development was interpreted as a beneficial action particularly on neural crest cells. Because the midline defects were unresponsive to methyl donor diet, the authors speculate that they arise from an independent pathological process [Billington et al, 2013]. Their model suggests that different structures are differentially sensitive to folic acid and methyl donor supplementation, with greater response in craniofacial and less in neural structures.…”
Section: Mechanisms and Mouse Models: Nutrient Modulation Of Neural Tmentioning
confidence: 99%
“…Many studies have demonstrated a link between folate deficiency during early pregnancy and developmental abnormalities, such as neural tube defects [10], abnormal embryonic development [11,12], and tumor formation [13]. For these reasons, dietary folate supplementation is routinely recommended during early pregnancy in human [14].…”
Section: Introductionmentioning
confidence: 99%